Certification - a difficult process? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
An organic vegetable exporter from Malawi explains the difficulties that small scale farmers may have if they want to export crops to foreign markets.